ASALIBU ISTIDLAL AN NUHAT FI KITAB SYARAH ALFIYAH IBNU ‘AQIL - Rauf, Abdullah Zainur; Qomari, Nur (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
Nahwu is the key to understanding Arabic texts. Nahwu is growing rapidly so that many nahwu experts write about nahwu theories. And among the experts, there are different views related to the rules of nahwu. This research aims to know the methods of thinking of grammarians in the book Sharh Alfiyah Ibnu â€˜Aqil. This research uses the qualitative approach to find out the differences between grammarians in controlling grammatical rulings. This research reveals five chapters in which scholars differ, including 1) presenting the subject over the subjunctive 2) abstracting the verb from a sign indicating the duality or plural 3) proving the t in the verb and its subject is an authentic feminine and with the separation of only 4) presenting the object on the subject 5) the return of the pronoun from The advanced subject is the delayed subject.Â